Optimalisasi Pencahayaan Alami Melalui Penerapan Void dan Skylight pada Gedung Terpadu UIN Sunan Kalijaga - Nimas Violina; Mohammad Sahid Indraswara; Chely Novia Bramiana (Universitas Diponegoro, 2025)
Energy consumption in the building sector, especially for lighting systems in tropical climates like Indonesia, is a crucial issue. The Integrated Building of UIN Sunan Kalijaga faces significant challenges regarding visual comfort and energy efficiency due to non-responsive facade design, resulting in low daylight penetration (